2012
DOI: 10.1371/journal.pone.0036883
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Is Associated with Coronary Artery Disease in Patients with Preserved Renal Function

Abstract: High serum phosphorus levels have been associated with mortality and cardiovascular events in patients with chronic kidney disease and in the general population. In addition, high phosphorus levels have been shown to induce vascular calcification and endothelial dysfunction in vitro. The aim of this study was to evaluate the relation of phosphorus and coronary calcification and atherosclerosis in the setting of normal renal function. This was a cross-sectional study involving 290 patients with suspected corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 36 publications
1
60
0
4
Order By: Relevance
“…In patients with normal kidney function who underwent coronary computed tomography, no correlation was found between FGF-23 levels and coronary artery calcification score or the presence of non-calcified plaques and coronary artery stenosis ≥50% [42]. In accordance with the above findings, another study in patients with preserved renal function reported no correlation between FGF-23 with either coronary artery obstruction or coronary artery calcification determined by coronary angiography and multislice computed tomography respectively [43]. In contrast, another study in patients undergoing coronary angiography reported a significant and independent from traditional risk factors association between FGF-23 levels and the stenosis scores as well as the plaque and dense calcium volumes [44].…”
supporting
confidence: 51%
“…In patients with normal kidney function who underwent coronary computed tomography, no correlation was found between FGF-23 levels and coronary artery calcification score or the presence of non-calcified plaques and coronary artery stenosis ≥50% [42]. In accordance with the above findings, another study in patients with preserved renal function reported no correlation between FGF-23 with either coronary artery obstruction or coronary artery calcification determined by coronary angiography and multislice computed tomography respectively [43]. In contrast, another study in patients undergoing coronary angiography reported a significant and independent from traditional risk factors association between FGF-23 levels and the stenosis scores as well as the plaque and dense calcium volumes [44].…”
supporting
confidence: 51%
“…Higher phosphate levels within the normal range are associated with vascular and valvular calcification in patients with moderate CKD, independent of PTH and calcitriol levels (86). In fact, higher serum phosphate concentrations falling within the normal range are associated with cardiovascular events and mortality in patients with normal and abnormal kidney function (9,87). A recent study by Shang et al (88) showed that hyperphosphatemia is an independent risk factor in the progression of coronary artery calcification.…”
Section: Phosphate and Cardiovascular Diseasementioning
confidence: 99%
“…These studies demonstrate that even a serum phosphate value within the reference range (0.8-1.4mmol/l) is associated with CV calcification, as well as increased CV risk [66]. Studies of older adults and CKD patients also found a significant association between higher serum phosphate and presence and extent of calcification 18,21,22,26,28,29 , with each 0.0323mmol/l rise in serum phosphorus being associated with 6.1% higher odds of having CAC 21 . Wang et al found a gender difference; in postmenopausal women, serum phosphate was significantly higher (1.15 vs 1.17 mmol/l) in subjects with AAC, while in older men there was no association 19 .…”
Section: Calcificationmentioning
confidence: 65%
“…Koreans with the highest calcium intake (>840mg/d) also had improved serum lipid profiles 20 . Many studies of serum calcium show no association with calcification [21][22][23][24][25] , although some show a positive correlation with presence, extent and progression of AAC in older adults 19,[26][27] , with mixed results for presence of CAC, although there may be an association with extent or progression [18][19][28][29] . Serum calcium was an independent predictor of calcified and mixed plaque but not non-calcified plaque 29 and higher concentrations were associated with lower in-hospital mortality among MI patients 30 .…”
Section: Calcificationmentioning
confidence: 99%